Java and XML - McLaughlin, Brett, ....- (Sebastopol (Calif.) : O'Reilly, 2001)
1.Introduction 2.Nuts and bolts 3.SAX 4.Advanced SAX 5.DOM 6.Advanced DOM 7.JDOM 8.Advanced JDOM 9.JAXP 10.Web publishing frameworks 11.XML-RPC 12.SOAP 13.Web services 14.Content syndication 15.Data binding 16.Looking forward
Keywords: Java (Computer program language).; Java (programmeertaal).; Web publishing; XML (Document markup language).